PENGARUH PEMBERIAN PUPUK ORGANIK DAN PUPUK ANORGANIK TERHADAP SERAPAN N, P, K OLEH TANAMAN JAGUNG PADA ULTISOL TAMBUNAN LANGKAT - Roswita Oesman; Fitra Syawal Harahap; Abdul Rauf; Rahmaniah Rahmaniah (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Maize is a cereal commodity that has an important role in supporting food security and food diversification programs. The application of organic and inorganic fertilizers is one of the efforts to increase national maize productivity. This study was aimed to explore the effect of the application of organic and inorganic fertilizers on N, P and K uptake by maize in an Ultisol. Treatments tested were combinations of five levels of organic fertilizer application (0%, 100%, 75%, 50%, and 25% of recommended organic fertilizer dose), and five levels of inorganic fertilizer (0%, 100%, 75%, 50%, and 25% of recommended inorganic fertilizer dose). The twenty-five treatments were arranged in a factorial randomized block design with two replications. Results of the study showed that there was a relationship between N, P and K uptake by maize with maize shoot dry weight, root weight, and shell weight. The highest plant height, shoot dry weight, and root dry weight of the maize were obtained by the treatment of 100% of organic fertilizer. The highest maize shell dry weight and uptake of N, P was obtained by the in the treatment of 75% organic fertilizer.